Standards for ethics in sport and exercise science research: 2018 update - Harriss, D. J.; Macsween, A.; Atkinson, G. (International Journal of Sports Medicine, 2017)
For publication in the International Journal of Sports Medicine (IJSM), studies involving human participants or animals must have been conducted in accordance with recognised ethical standards and national/international laws. At the very first stage of paper submission, authors are required to adhere to these and all other relevant standards and laws.